Synonymies, new records, and new species in Cerambycinae (Coleoptera, Cerambycidae) - Heffern, Daniel; Botero, Juan Pablo; Santos-Silva, Antonio (Zootaxa, 2020)
New synonymies in Clytini: Clytopsis Casey, 1912 is synonymized with Ochraethes Chevrolat, 1860; and Ochraethes nigritus Bates, 1892 is synonymized with O. viridiventris (Chevrolat, 1860). New records: Neoclytus acteon (Chevrolat, 1860) (Clytini) is reported for the first time from Nicaragua; and Heterachthes hildebranti Galileo & Santos-Silva, 2016 (Neoibidionini, Compsina) is reported for the first time from the Mexican state of Jalisco. New species: Ochraethes nevadensis sp. nov. (Clytini) is described from the United States of America (Nevada); Psyrassa audureaui sp. nov. (Elaphidiini) is described from Mexico and Nicaragua; Oxylymma rileyi sp. nov. (Rhinotragini) is described from Panama.